Bare It All - Foster, Lori, 1958- (Don Mills, Ont. : Harlequin HQN, 2013)
"As the person responsible for taking down a brutal human trafficker, Alice Appleton fears retaliation at every turn. No one knows about her past, which is exactly how she prefers it--until the sexy cop next door comes knocking"--P. [4] of cover.
Keywords: Police -- Fiction; Human trafficking; Fiction; Man-woman relationships -- Fiction; Thrillers (Fiction); Romance fiction